Reconstructing Salafi epistemology through at-taṣfiyah and at-tarbiyah: A conceptual framework for contemporary Islamic thought - Faelalika Putri Herhan; Amirul Bakhri (Mishkat: Journal of Theology and Civilization, 2026)
Debates regarding the relevance of Manhaj Salaf in addressing contemporary issues reveal a conceptual gap, as the relationship between its epistemology and the concepts of at-taṣfiyah and at-tarbiyah has not been comprehensively explained. This study aims to examine the relationship between the epistemology of Manhaj Salaf and the concepts of at-taṣfiyah and at-tarbiyah, as well as their implementation in responding to contemporary issues. A qualitative approach employing library research was adopted, and the data were analyzed using content analysis. The findings demonstrate that the epistemology of Manhaj Salaf provides the foundation for at-taṣfiyah as a process of doctrinal purification and at-tarbiyah as a process of continuous educational development, thereby forming a systematic framework for responding to pluralism, liberalism, artificial intelligence, bioethics, financial technology, and environmental issues. This study contributes by proposing a conceptual framework that integrates these three concepts into an analytical model for understanding how Manhaj Salaf responds to the dynamics of contemporary society. Abstrak Perdebatan mengenai relevansi Manhaj Salaf dalam merespons isu-isu kontemporer masih menyisakan kesenjangan konseptual karena hubungan antara epistemologi, at-taṣfiyah, dan at-tarbiyah belum dijelaskan secara terpadu. Penelitian ini bertujuan menganalisis hubungan antara epistemologi Manhaj Salaf dengan konsep at-taṣfiyah dan at-tarbiyah, serta menjelaskan implementasinya dalam merespons berbagai isu kontemporer. Penelitian ini menggunakan pendekatan kualitatif dengan metode library research, sedangkan data dianalisis menggunakan teknik content analysis. Hasil penelitian menunjukkan bahwa epistemologi Manhaj Salaf menjadi landasan yang mengarahkan at-taṣfiyah sebagai proses pemurnian ajaran dan at-tarbiyah sebagai proses pembinaan berkelanjutan sehingga membentuk kerangka respons yang sistematis terhadap pluralisme, liberalisme, kecerdasan buatan, bioetika, teknologi finansial, dan isu-isu lingkungan. Penelitian ini berkontribusi dengan menawarkan kerangka konseptual yang mengintegrasikan ketiga konsep tersebut sebagai model analitis untuk memahami respons Manhaj Salaf terhadap dinamika masyarakat modern.